OVERVIEW OF FAMILY SUPPORT FOR MENTALLY DISORDERED PATIENTS IN THE MENTAL POLYCLINIC OF JAMBI PROVINCE RSJD - Eva, Eva Daya Nababan; Kamariyah; Yuliana (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
The prevalence of mental disorders continues to increase, therefore mental disorders are a serious health problem. Data obtained from the Jambi Prov Hospital, patients with schizophrenia in 2020 were 5606 visits (76%), in 2021 there were 13,438 visits (77%), and in 2022 there were 3,442 visits (78%). Treatment of patients with mental disorders requires a long time and process, so it requires the role of the family as the unit closest to the patient to provide support in the patient's healing process. The purpose of this study was to obtain an overview of family support for patients with mental disorders at the Psychiatric Polyclinic of the Jambi Prov Hospital. This research design is descriptive using a survey approach. The population of this study were mental patients who were undergoing treatment at the Psychiatric Polyclinic of the Jambi Province Hospital. The sample used was 107 people with accidental sampling technique. The instrument used was a family support questionnaire sheet with univariate analysis. Based on the results of the study, the description of family support for patients with mental disorders as a whole was categorized as good (97.2%) of respondents. The components of emotional support and appreciation were good (94.4%) of respondents, quite good (4.7%) of respondents and not good (0.9%) of respondents. Instrumental support in good category (97.2%) of respondents., quite good (2.8%). Information support is in the category good (80.4%) of respondents, quite good (17.8%) of respondents, and not good (1.9%) of respondents. Data analysis shows that information support is the lowest family support. It is hoped that this research will become an evaluation and input for the Jambi provincial RSJD, and future researchers.